The Pathological Study of Amputated Limbs Infected by Pythium insidiosum: To Propose Adequacy of Surgical Margins - Sangruchi, Tumtip (Siriraj Medical Journal, 2016)
Objective: Arterial pythiosis, caused by Pythium insidiosum, is a life-threatening condition. The lesions usually involve main arteries of the lower extremities, which extend to the abdominal aorta. Early amputation is required to save patient’s life. The adequacy of amputation needs to ensure that the resection margins are devoid of the organisms. The aim of this study is to suggest the level that should be devoid of organisms for surgical amputation. Methods: We studied amputated limbs of patients diagnosed as arterial pythiosis. The major arteries of the limbs were dissected, then serial cross cut at 0.3-0.5 cm intervals, and consecutively submitted from proximal to distal segments for routine tissue processing and staining. Segments of non-inflamed vessels continuing above or below the level of arterial occlusion were identified. To demonstrate fungal-like hyphae, all corresponding blocks of non-inflamed arteries were stained with Grocott’s methenamine silver staining (GMS) and thoroughly examined under a microscope. Results: From June 2010 to June 2011, there were 4 cases of arterial pythiosis. Chronic arteritis obliterans, acute necrotizing arteritis with thrombosis, or a ruptured aneurysm was demonstrated from distal to proximal segments without skip lesions. At the level of 5 cm. from the occlusion, neither arteritis nor fungal-like hyphae was identified. Conclusion: Based on the evidence from only 4 cases, we have proposed that at 5 cm. or more above the occlusion, the noninflamed arteries were free of P. insidiosum, while fungal hyphae might be observed in inflamed soft tissue.